Особенности наномодифицирования многокомпонентных сплавов - Калинин, Александр Васильевич (НТУ "ХПИ", 2015)
Разработана технология модифицирования алюминиевых и никелевых сплавов нанодисперсными композициями. Построены сравнительные гистограммы механических свойств деформированных алюминиевых сплавов до и после модифицирования. Обоснованный выбор типа наномодификатора и способ его таблетирования. Для алюминиевых сплавов рекомендован нанодисперсный карбид кремния β-SiC, для никелевых сплавов-нанодисперсный карбонитрид титана TiCN фракцией 50...100 нм. В модифицированных сплавах получено значительное измельчение дендритной и зеренной структуры. В результате модифицирования достигнуто повышение механических свойств.

The technology of modifying aluminum and nickel alloys nanodispersnymi compositions. Built comparative histogram of the mechanical prop-erties of deformed aluminum alloys before and after modification. Reasonable choice of type and method of nanomodifier tableting. Nanodispersed modifiers were prepared by plasma chemical synthesis by varying the temperature and time mode and the composition of gas-plasma flow. Deter-mined by the specific surface obtained refractory compounds. Features size and crystallographic parameters were studied by electron microscopy and diffraction analysis. For aluminum alloys recommended nanosized silicon carbide β-SiC, for nickel alloys - titanium nanodisperse carbonitrile TiCN fraction 50 ... 100 nm. Comparison of images of particles β-SiC with their micro diffraction patterns showed that the main habit plane is the base plane (0001), and the cut is carried out by planes of {1010}. The modified alloys obtained by grinding a significant dendrite and the grain structure. The improvement is achieved by modifying the mechanical properties.
Features of nanomodified multicomponent alloys
Keywords: наномодификаторы; химический состав; неметаллические включения; карбонитрид титана; карбид кремния; nanomodifiers; chemical composition; non-metallic inclusions; itanium carbonitride; silicon carbide